Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1159/000326629
|View full text |Cite
|
Sign up to set email alerts
|

Early Predictors of Separation Anxiety Disorder: Early Stranger Anxiety, Parental Pathology and Prenatal Factors

Abstract: Separation anxiety disorder (SAD) is defined as anxiety over being away from a loved one, usually a parent, and is one of the most common anxiety disorders in children under 18 years of age [1] , with median prevalence rates between 1.09 and 4.1% in English-speaking children aged 5-11 [2-4] and 0.75% in Swiss children aged 7-16 years [5] . Further, SAD is a well-established predictor of later psychopathology, including depression, panic dis order with and without agoraphobia [6][7][8] , generalized anxiety dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 70 publications
0
7
0
4
Order By: Relevance
“…These results support a developmental psychopathology conceptualization of anxiety disorders, a perspective that is expected to be strengthened in DSM-5 (47). Preliminary evidence suggests a developmental pathway that may start with exaggerated stranger anxiety in infancy (48). Understanding stranger anxiety as an age-dependent developmental task may provide new insight to our understanding of the etiology of separation anxiety disorder.…”
Section: Discussionmentioning
confidence: 99%
“…These results support a developmental psychopathology conceptualization of anxiety disorders, a perspective that is expected to be strengthened in DSM-5 (47). Preliminary evidence suggests a developmental pathway that may start with exaggerated stranger anxiety in infancy (48). Understanding stranger anxiety as an age-dependent developmental task may provide new insight to our understanding of the etiology of separation anxiety disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Separation anxiety typically starts to manifest at about 8 months, with a peak around 13 months, and a decrease from 30 months onwards (see also Hock & Lutz, 1998). When separation anxiety is excessive and persists beyond infancy, this may signal deficiencies in the quality of the 4 parent-child relationship (e.g., preoccupied attachment) and it may forecast separation anxiety disorder and poor adjustment and ill-being later in life (e.g., Bernstein & Borchardt, 1991;Brumariu & Kerns, 2010;Dallaire & Weinraub, 2005;Lavallee et al, 2011). Increasingly, it is being argued that separation anxiety is relevant in later developmental periods as well.…”
Section: Separation Anxiety In Family Relationshipsmentioning
confidence: 99%
“…parent-child relationship (e.g., preoccupied attachment) and it may forecast separation anxiety disorder and poor adjustment and ill-being later in life (e.g., Bernstein & Borchardt, 1991;Brumariu & Kerns, 2010;Dallaire & Weinraub, 2005;Lavallee et al, 2011). Increasingly, it is being argued that separation anxiety is relevant in later developmental periods as well.…”
mentioning
confidence: 99%
“…One study examined whether early stranger anxiety could differentiate youth with SAD from those without [ 40 ] . This study found that parents of children with SAD (ages 4-14) described their children as having greater stranger anxiety as toddlers than parents of youth without SAD.…”
Section: Early Developmental Factorsmentioning
confidence: 99%